2022
DOI: 10.1093/ckj/sfac046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of an intradialytic exercise programme on sarcopaenia in very elderly haemodialysis patients

Abstract: Sarcopenia is a highly prevalent condition in persons on hemodialysis. In stable very elderly (75- to 95-year-old) persons on chronic hemodialysis, we prospectively studied the European Working Group on Sarcopenia in Older People (EWGSOP2) steps stability over time in 37 controls and their response to a 12-week intradialytic lower limb exercise program in 23 persons. Overall dropout was 15% and the main cause for dropout was death (8%). Thus, 33 controls and 18 exercise participants were evaluated at 12 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…While initially the concept of sarcopenia focused on muscle size, muscle strength does not depend on muscle size alone, and the two entities can be separate [ 20 , 21 ]. Indeed, the loss of strength is greater than the loss of muscle mass in older patients, and strength can decrease while muscle size is still maintained or even increased [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…While initially the concept of sarcopenia focused on muscle size, muscle strength does not depend on muscle size alone, and the two entities can be separate [ 20 , 21 ]. Indeed, the loss of strength is greater than the loss of muscle mass in older patients, and strength can decrease while muscle size is still maintained or even increased [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taichi exercises increase the ability of muscles to extend/stretch as much as possible so that the body can move with a maximum range of motion without discomfort/pain (Sánchez-Tocino et al, 2022). Increased flexibility is closely related to soft tissues, such as ligaments, tendons, muscles, and bone structure (Xinzheng, Fanyuan, & Xiaodong, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed significant changes in hemoglobin and albumin levels, which aligns with previous research. [23][24][25][26][27][28][29][30][31] The sample size can be expanded in future studies to investigate whether exercise can help to control anemia in hemodialysis patients. It is important to note that adequate dialysis and complication management are essential for exercise and psychological rehabilitation.…”
Section: Before the Interventionmentioning
confidence: 99%